PELUANG DAN KENDALA BUDIDAYA IKAN LELE DALAM KONTEKS PEMBERDAYAAN MASYARAKAT - Andri Anashrullah; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Intrinsically, the empowerment of society is not a new thing. This attempt to intensify the society has been happening due to the desire and the effort from the regional government to develop its region to be developed in a long term. In this case, the phenomenon that is found in Hangtuah village is a society empowerment engaged in the field of catfish cultivation and how big is the opportunity that could possibly be expanded on catfish cultivation. In a research, there are a lot of approach that could be used, this research uses qualitative research method with the approach of “purposive sampling”, aiming to understand and depict certain societal phenomenons and tend to analyze it based on an obtained data. Basically, there has already been a lot of empowerment that is developed according to the stages listed on the theory of Robert K. Merton, but then again it is needed more support in the form of attendant and training for the businessmen, material form of aid (development supporting tools or material), so that it could constantly maximize all the existing potential from the catfish cultivation itself.Keywords: empowerment society, catfish cultivation, adaptation typology